Introduction to the Issue on Computational Models of Memory: Selected Papers From the International Conference on Cognitive Modeling. (13th January 2017) - Reitter, David; Ritter, Frank E.
Abstract : Computational models of memory presented in this issue reflect varied empirical data and levels of representation. From mathematical models to neural and cognitive architectures, all aim to converge on a unified theory of the mind.